Habitat requirements of Boreal Owl (Aegolius funereus) and Pygmy Owl (Glaucidium passerinum) in mountainous populations on the Balkan Peninsula :Powerpoint - Stoyanov, S.I. (University of Twente, 2020)
This lecture presents: Map of Bulgaria with georeferenced image of high resolution satellite imagery of the study area from Google- ; Shiroka Laka Forest Enterprise in “Trigrad-Mursalitsa” Natura-2000 zone according to the Birds Directive; Two species of boreal owls; Data collection – birds; Data collection – stand parameters; Predictor variables; Explanatory variables - Boreal Owl.